Clinical Aspects of Opium Adulterated with Lead in Iran: A Review. Issue 1 (18th October 2017) - Alinejad, Samira; Aaseth, Jan; Abdollahi, Mohammad; Hassanian‐Moghaddam, Hossein; Mehrpour, Omid
Abstract: Adulteration of drugs with poisonous substances during production or consumption has caused numerous health problems. Among contaminants that have the potential of producing poisonous effects are the heavy metals lead, arsenic and thallium that make up an important group of toxic substances. The emergence of these new health problems related to opioid abuse has precipitated this MiniReview on the status of the most hazardous and common opioid adulterants. In fact, adulterated opium is a major public health problem and can threaten the health of users. In this study, we searched for information on opium, opiates, lead poisoning, toxicity, intoxication, Iran and heavy metals in the TUMS Digital Library, PubMed, Scopus, EMBASE and Google Scholar bibliographical databases. This MiniReview primarily included articles on lead poisoning, signs and symptoms, and management in opioid‐dependent individuals. Exclusion criteria were articles dealing with animal studies, specific paediatric studies, adulterants other than heavy metals and substances other than opioids. Adulterated opium is one of the new sources of exposure to lead and has precipitated an increase in lead‐poisoned cases owing to the widespread use of opium. The toxicology of lead and general guidelines on diagnosis and treatment of lead poisoning is briefly reviewed. The symptoms of lead toxicity mimic several diseases often leading to unnecessary diagnostic methods, misdiagnoses and even surgery. Finally, owing to the fact that lead toxicity shows non‐specific signs and symptoms, screening for this disease, by taking blood samples and assessing blood lead levels in high‐risk people, should be given an utmost priority. It is recommended that screening tests are adopted and applied for any drug‐abusing patient with non‐specific subacute signs and symptoms like abdominal pain, constipation and anaemia.